Investigating the shared genetic information between serum concentration levels of liver enzymes and cholelithiasis - Tian, Wenhao; Wu, Zixin; Yang, Wen; Wang, Hongyang; Feng, Qiyu (BMC gastroenterology, 2025)
Liver injury is associated with cholelithiasis, with changes in liver enzyme levels potentially influencing cholelithiasis risk. This study investigates the shared genetic basis between serum levels of four liver enzymes and cholelithiasis using summary data from large-scale genome-wide association studies (GWAS). We assessed genetic correlation between liver enzymes and cholelithiasis, and performed local genetic correlation analysis to identify shared genomic regions. A cross-trait meta-analysis identified significant SNPs (single nucleotide polymorphisms) shared between the enzymes and cholelithiasis. To explore causal effects, we applied both two-sample Mendelian randomization and multivariable Mendelian randomization. Heritability-based enrichment analysis was employed to identify tissues and cells jointly associated with liver enzymes and cholelithiasis, while summary-data-based Mendelian Randomization (SMR) was utilized to identify shared genes. Alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT) showed relatively stronger genetic correlations with cholelithiasis compared to the other liver enzymes. Shared SNPs were identified among ALT, GGT, alkaline phosphatase (ALP), and cholelithiasis. Mendelian randomization indicated that a tenfold increase in ALT could raise cholelithiasis risk by 203.4%. The liver was identified as the primary tissue linking these enzymes to cholelithiasis, but no shared cell types were implicated. Several candidate genes, such as SPTLC3, may jointly influence liver enzyme levels and cholelithiasis risk. Elevated ALT levels may increase cholelithiasis risk. Genetic associations across tissues, genes, and SNPs suggest that liver enzymes could mediate the relationship between liver injury and cholelithiasis risk, providing insights into shared genetic mechanisms with potential implications for future research.